Cultura escrita e instrução Pública Primária no pernambuco imperial (1837-1889) - Matias, Thiago Trindade (2015)
The culture of writing history, specific form of cultural history, aims to interpret the social practices of reading and writing (CASTILLO GOMEZ, 2003). This thesis, from the point of view of its objectives, investigates, from the social uses, empirical media culture of writing memory, produced for / by primary public instruction in Pernambuco nineteenth century, in the period 1837-1889, this is what was written, who wrote, for whom it was written, for what was written in / for primary public education. In order to achieve this purpose, this research is part of the cultural perspective of history writing as Castillo Gómez (2003), and from the perspective of cultural history, that "[...] is mainly identifies the way in different places and times a particular social reality is constructed, thought given to read. "(CHARTIER, 2002). This work of the discussion focused on the relationship memory, document and history, consolidated by cataloging all collected sources. Of printed manuscripts, much of the documentation was collected in the State Public File Jordan Emerenciano (APEJE - PE) and part in Nabuco Foundation (FUNDAJ - PE), and the dialogue established with memories, autobiographies, testimonials and iconographic sources. This research contributes to the social history of written culture in Brazil, and to cooperate with the field of the history of education to collect data of the institution 'school' and didactic-methodological processes prevailing at the time in the nineteenth century, for the teaching of reading and writing. As for the results obtained, it is considered that the writing relationship between culture and the primary public instruction in Pernambuco Imperial, configured, in general, for the ordering and tax for the particular order of say and do. The educational legislation, as one of the scriptural material objects domain (CARDONA, 2013) of public instruction, determined teaching methods, curriculum and testing programs, necessary utensils to school, guidance as to space and school time, in addition to models writing that would fit writing to writing professionals: managing director, literary representative, secretary, inspector of public instruction, teachers. As for the charges for teaching, reading and writing were the means by which it sought to impose the educational system, which received direct influence of political ideologies at the time, is in search of a conditioned education to moral and religious values, is trying to meet the ideals of a formation of the modern man. The written documentation coming from the control and institutional discipline was one of the strategies by which the primary public education sought to establish itself as a strong and effective institution in order to systematize the power of independent state and will soon become would Republican. All these actions were defined as forms and ways of framing the bodies in specific order of say and do the education, thereby potentially through domination, control and discipline the proposed education model.